Characteristics and scenarios of solar energy development in Iran: Fuzzy cognitive map-based approach. (December 2019) - Alipour, Mahdi; Hafezi, R.; Papageorgiou, E.; Hafezi, M.; Alipour, M.
Abstract: Widespread use of promising solar energy is an integral attribute of governments toward global efforts in mitigating future emission and reducing the fossil fuel consumption trajectory. However, the outlook of solar energy development at the strategic level is driven by inherent uncertainties in a long-term perspective. As these unpredictable volatilities come into play, they heavily influence the future trends formed by a range of exogenous and endogenous factors including Political, Economic, Social, Technological, Environmental, and Legal (PESTEL). This study aimed at identifying, characterizing, and analyzing influential PESTEL factors shaping the dynamics of Solar Photovoltaics (SPV) in an uncertain environment. For this purpose, the Fuzzy Cognitive Mapping (FCM) method was employed for the case of Iran to investigate how involved factors dynamically interact and collectively behave in system. A participatory stepwise framework was developed consisting of three steps by conducting a survey and two workshops with the participation of multidisciplinary stakeholders. Aa a result, a semi-quantitative model was formed in an integrated FCM comprising 31 interwoven concepts. To further outline possible future trends, five key concepts were determined that explored four plausible projections of Iran's SPV sector. The scenario outcome suggests that the industry is profoundly affected by external economic and political factors. Two scenarios "Cornered in a Dead-End" and "At Wits' End" project that, by 2030, the sector experiences a declining growth trend. "The Period of Tolerance" scenario does not envisage a dramatic change from the current trajectory, while in only "Blue Sky" the country's SPV sector anticipate a moderate growth. Highlights: Fuzzy cognitive Map for analyzing development of solar energy at national level. Studying characteristics and dynamics of solar technology deployment in an uncertain environment. As a case study, Iran's solar sector is heavily driven by political and economic parameters. Two scenarios project a declining growth trend while one scenario expects a moderate growth.